Logistics and supply chains in emerging markets - Manners-Bell, John (Kogan Page, 2014)
"Emerging markets hold the key to the advancement of the global logistics industry over the next twenty years. While developed economies struggle to come to terms with huge levels of debt, newly industrialized markets are showing strong growth prospects as manufacturers and investors look at low cost production locations. This, in turn, has led to urbanization and the rise of more affluent middle classes in regions such as the Middle East, Africa, Latin America and Asia.John Manners-Bell analyzes the key trends affecting the development of emerging markets: the social, economic and political context; the reasons behind their integration within the global trading economy; and the main challenges (security, corruption and transportation infrastructure). He includes individual sections on the BRIC transport and logistics sectors, as well as prospects for Asia, Latin America, Africa and the Middle East. He also provides a survey section showing the best markets to invest in and a downloadable index comparing the world's major developing logistics markets on a number of different metrics identifying the key attributes that make the markets an attractive investment proposition. "--